A ferrocene-containing analogue of the MCU inhibitor Ru265 with increased cell permeability. Issue 2 (6th December 2022) - Huang, Zhouyang; Spivey, Jesse A.; MacMillan, Samantha N.; Wilson, Justin J.
Abstract : An analogue of the mitochondrial calcium uniporter (MCU) inhibitor Ru265 containing axial ferrocenecarboxylate ligands is reported. This new complex exhibits enhanced cellular uptake compared to the parent compound Ru265 . Abstract : The mitochondrial calcium uniporter (MCU) is a transmembrane protein that mediates mitochondrial calcium ( m Ca 2+ ) uptake. Inhibitors of the MCU are of interest for their applications as tools to study the role of m Ca 2+ uptake on cellular function. In this study, we report two potent MCU inhibitors, [Ru2 (μ-N)(NH3 )8 (FcCO2 )2 ](OTf)3 (RuOFc, Fc = ferrocene, OTf = triflate) and [Ru2 (μ-N)(NH3 )8 (PhCO2 )2 ](OTf)3 (RuOBz ). These compounds are analogues of the previously reported inhibitor [Ru2 (μ-N)(NH3 )8 (Cl)2 ](Cl)3 (Ru265 ) that has been derivatized with ferrocenecarboxylate and benzoate ligands, respectively. Both compounds were synthesized and fully characterized by NMR spectroscopy, infrared spectroscopy and X-ray crystallography. Under physiological conditions, RuOFc and RuOBz aquate with half-lives of 2.9 and 6.5 h, respectively, to produce [Ru2 (μ-N)(NH3 )8 (H2 O)2 ](OTf)5 (Ru265′ ) and the free carboxylates. Cyclic voltammetry of RuOFc in N, N ′-dimethylformamide (DMF) reveals a prominent reversible 2e − transfer event at 0.64 V vs. SCE, corresponding to the simultaneous oxidation of both ferrocene-containing axial ligands. All three complexes also exhibit irreversible Ru-based reductions at potentials below −1 V vs. SCE. DFT calculations of Ru265′, RuOFc and RuOBz confirm that the redox activity of RuOFc arises from the ferrocene ligands. Furthermore, LUMO energies of the three compounds correlate with their irreversible reduction potentials. A systematic comparison on the biological properties of Ru265, RuOFc and RuOBz was carried out. Both RuOFc and RuOBz inhibit m Ca 2+ uptake in permeabilized HEK293T cells, but are 5–7 fold less potent than Ru265 . In intact cells, RuOBz is taken up by cells and inhibits the MCU to a similar extent as Ru265. RuOFc, however, exhibits a 10-fold increase in cellular uptake over Ru265, which in turn also leads to a modest enhancement in MCU-inhibitory activity in intact cells. Moreover, in contrast to Ru265, RuOFc is cytotoxic to HEK293T and HeLa cells with 50% growth inhibitory concentration values of 23.2 and 33.9 μM, respectively, a property that could be leveraged to develop MCU-targeting anticancer agents. These results establish RuOFc as a potent MCU inhibitor and another example of how axial ligand functionalization of Ru265 can lead to new compounds within this class with diverse physical and biological properties.